Potential of silymarin and its polyphenols to affect Nrf2 signalling pathway in human skin cells - Rysava, Alena; Valentova, Katerina; Cizkova, Katerina; Vostalova, Jitka; Zalesak, Bohumil; Rajnochova Svobodova, Alena (Biomedical papers, 2025)
Introduction. Human skin is constantly exposed to various agents causing oxidative stress. In response, skin cells can activate transcriptional nuclear factor erythroid 2-related factor 2 (Nrf2), which influences the expression of several protective genes. However, accumulating evidence suggests severe adverse effects of chronic Nrf2 activation. Phytochemicals are popular for supporting skin health. Some are potent Nrf2 inducers and their long-term use may be hazardous. Silymarin (SM), an extract from Silybum marianum fruits, and its major flavonolignan silybin (SB) are used in cosmetic formulations for their protective and regenerative activities. However, knowledge about their potential to modulate Nrf2-driven pathway in skin cells or tissue is lacking.Methods. Here we evaluated effects of SM, SB, silychristin (SC), silydianin (SD), isosilybin (ISB) and 2,3-dehydrosilybin (DHSB) and taxifolin (TA) on Nrf2 nuclear translocation, the level of Nrf2-control proteins (Keap1 and Bach1) and selected Nrf2-driven genes (NAD(P)H:quinone oxidoreductase 1 and heme oxygenase 1) in human primary fibroblasts and keratinocytes.Results. SM and its components significantly stimulated Nrf2 nuclear translocation; SM and SB were most potent on both cell types. The effect of SM and compounds was more pronounced in fibroblasts than on keratinocytes. Regardless, effects of SM and studied compounds on the Nrf2 regulating and Nrf2-controled proteins were non-significant.Conclusion. SM and its components do not have a significant effect on the studied proteins, and seem to be safe with respect to possible negative effects associated with the Nrf2 signalling pathway activation during dermal application. However, we cannot give a definitive answer on their effect after repeated long-term application to the whole skin. Further experiments on human skin ex vivo or clinical studies on volunteers are necessary.
Keywords: flavonolignan; flavonoid; nuclear factor erythroid 2-related factor 2; primary fibroblasts; primary keratinocytes; silymarin